PORTAL INFORMASI SOLUSI KOMUNIKASI EFEKTIF MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA - Raden Wirawan; Sitti Arni; Agussalim Patola DM (Rumah Jurnal STAIN Majene, 2025)
Information technology has the potential to change the way villagers interact in the implementation of development, having an effective communication system to ensure meaningful and targeted interactions. This study aims to determine the information portal as an effective communication solution in increasing community participation in village development in Tanakaraeng Village, Manuju District, Gowa Regency. The current information system still relies on manual methods, which results in delays in data processing and difficulty in accessing the community. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. Observations were conducted to understand the operation of the existing system, interviews with the Village Head, village officials, and the community to identify problems and needs, and documentation studies to explore data related to village development. The results of the study indicate that information portals can increase participation and facilitate access to information for the community so that communication becomes more effective according to the results of the UAT analysis which was stated as acceptable with an average score of 3.5. This study provides recommendations for designing a more efficient web-based information portal, which is expected to increase transparency, accountability, and community participation in the village development process.